One new species of Eremus Brunner von Wattenwyl, 1888 (Orthoptera: Gryllacrididae) from China - Yang, Zizhong; Jing, Liu; Bian, Xun (Zootaxa, 2020)
One new species of Eremus Brunner von Wattenwyl, 1888 is reported from Southwest China, Yunnan. The morphological features are described, and provided with colored charts of classification features. Up to now, only two species have been described in the Chinese fauna. Type specimen is deposited in the Institute of Entomoceutics Research, Dali University (DUIER).